Izkušnje bivanja in dela sodobnih slovenskih izseljencev v Avstriji in Nemčiji - Gostič, Maja (Dve domovini, 2019)
The article deals with the subjective perceptions of emigrants that left Slovenia between 2014 and 2017. Their experiences of their stay in Austria and Germany, which are the most popular destinations for contemporary emigrants from Slovenia, are presented in depth. The subjective experiences of migrants are important for under-standing the broader picture of contemporary economic migration with the support of objective statistical data. The purpose of the research was to obtain as much in-formation as possible on the migration experience from the perspective of our con-temporary times affected by globalization and mobility. The research contributes to an understanding of the contemporary motives for and experiences of emigration in the EU.
Keywords: 21.st.; 21st century; Austria; Avstrija; economic migration; ekonomske migracije; Germany; Nemčija; Slovenci; Slovenian emigration; Slovenians; slovenski izseljenci; subjective experiences; subjektivne izkušnje